“NIVEL DE EMPATÍA ENTRE PARES EN LOS ESTUDIANTES DE LA UNIDAD EDUCATIVA “CARLOS CISNEROS”. RIOBAMBA, PERÍODO OCTUBRE 2018 – MARZO 2019” - Ibarra Marca, Thalia Mishelle (2019)
The objective of this study was to determine the levels of empathy among peers in Third Year Baccalaureate "A" students of the Educational Unit "Carlos Cisneros". Riobamba, Period October 2018- February 2019, we worked with 68 students, empathy is important for people in their interpersonal relationships, understands the emotions and feelings of the individuals around us, trying to objectively experience what the other person feels , in its general classification it has two cognitive and affective levels. Methodologically, a quantitative approach was used; the design is non-experimental; having as type of investigation by the objects: basic, by the place it is of field, by its time: transversal; also by its level and scope is descriptive and correlational, the study population were students of the Educational Unit "Carlos Cisneros"; the sample was intentional non-probabilistic; the technique used was the Psychometric Test, the instrument used was the TECA Cognitive and Affective Empathy Test, which facilitated the interpretation and analysis of empathy, it was allowed to reach the result that adolescents have a low level of empathy, where as a result in the comparison men have higher levels unlike women in the dimensions adoption of perspectives, emotional understanding, empathic stress and empathic joy.